Perilaku Pengelolaan Keuangan Berbasis Green Economy - Tasya Wardani; Reza; Ratna Fitri Astuti (Ekuitas: Jurnal Pendidikan Ekonomi, 2022)
Financial management behavior has a tremendous impact on an individual's future and alternatives to avoid excessive financial problems. Furthermore, sustainable consumption and production patterns can apply efficiency to use resources, live with minimum waste and live clean in every aspect of life. However, in reality, students have economic activities that choose everything instantaneous to meet their needs with buying food instead of cooking it. The type of study conducted was descriptive qualitative research. The data collection was conducted by interviewing the Department of Social Science Education students, Faculty of Teacher Training and Education, Mulawarman University class 2018-2021, who lived in boarding houses. The data analysis consists of three activity, data reduction, data display and conclusion drawing. Based on the findings, it was known that students tended to think less about green economy-based financial management behavior and only focused on financial management behavior without thinking about their environment. Students waste resources that can harm their environment, and they only choose to save on products that have benefits for themselves and do not think about the benefits for their surroundings that students tend no to turn off electronic devices after use. Therefore, students should start to be able to minimize the waste of resources that can harm their surroundings and think more about their environment.